Sistem Manajemen Konferensi Ilmiah Berbasis Web Menggunakan Metode Pengembangan Waterfall - Utomo, Muhammad Nur Yasir (Jurnal Teknologi Elekterika, 2022)
Scientific publications are a means of delivering research results and innovations of researchers. Recently, researchers' interest in publishing publications is also increasing. This increase occurred in the publication of papers through scientific conferences. This encourages the need for the use of information technology to facilitate conference management. However, the application of the conference management system is still minimal. Based on these problems, this study proposes a web-based conference management method. The system is built using a MySQL database and Model-View-Controller (MVC) code architecture in PHP. Therefore, every conference process can be included in the system. the system is designed with three main modules, namely the participant/presenter module, reviewer module, and committee/admin module, which covers the entire conference process starting from registration, paper submission, review, payment and distribution of presentation rooms. Trials and evaluations are carried out using the Black Box Testing method to ensure the system can work well. The results of the tests and evaluations that have been carried out show that the proposed system is proven to have good performance with a score of 100% or successfully fulfills all existing test scenarios